Pengaruh Ekspor Migas Terhadap Pertumbuhan Ekonomi di Asia Tenggara - Arumsari, Maritza; Zakaria, Rinny Apriliany; Rahajuni, Dijan (Universitas Indraprasta PGRI, 2025)
Crude oil exports are still a milestone in Southeast Asian countries in driving trade balance surpluses and stimulating economic growth. However, the performance may differ depending on macroeconomic factors. Therefore, this study aims to examine how crude oil exports affect economic growth in Southeast Asian countries using Error Correction Model (ECM) analysis. The results show that crude oil exports positively affect economic growth in Southeast Asian countries in the short and long term. Thus, government policy focuses on encouraging domestic crude oil production for export, while controlling several macroeconomic variables, such as inflation and investment.